MEMAHAMI POLITIK GLOBALISASI DAN PENGARUHNYA DALAM TATA DUNIA BARU: ANTARA PELUANG DAN TANTANGAN - Mohammad Maiwan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2014)
Actually globalization constitute of growth process having the character of  accelerate and extend, influencing way of living, view, and also human desire which always change. This phenomenon represent phase from modernization, what basically reorganizing of various life facets. Globalization entangle elements which each other related and form configuration of the universally new order. Globalization not merely transformed society in new progress and bring of positive creativities, but at the same time generate negative impacts. Various globalization impact  namely: Integration, standardization, transparency, homogenization, and strenghend of local identities which stem from local tradition and values.